Republic of Poland : Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The 2008 transition to the new banking supervisory framework in Poland has been relatively smooth, and the banking system has proven effective in weathering the financial crisis. This assessment focuses on the working of the Polish Financial Supervision Commission (KNF), which is responsible for banking supervision in Poland. KNF has undertaken numerous proactive measures to preserve financial sector stability during the crisis. As a priority, KNF's interaction with bank auditors as well as with supervisory board members should also be strengthened.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet